ChemInform Abstract: Copper‐Catalyzed P‐Arylation via Direct Coupling of Diaryliodonium Salts with Phosphorus Nucleophiles at Room Temperature. Issue 1 (7th January 2014) - Xu, Jian; Zhang, Pengbo; Gao, Yuzhen; Chen, Yiyin; Tang, Guo; Zhao, Yufen
Abstract This new method provides a very simple and high‐yielding access to different substituted phosphine oxides and phosphonates within short reactions times.